Implementation of The Fourth Industrial Revolution (IR 4.0) For Controlling Workers’ Safety at Construction Site - Hanuar, Nur Nasrin Azmah; Kasim, Narimah; Zainal, Rozlin; Abd Rahim, Mohd Hilmi Izwan; Mat Jusoh, Zairra (Research in Management of Technology and Business, 2023)
The adoption of technology associated with the Fourth Industrial Revolution (IR 4.0) is seen as a main factor in the construction industry's increased reliance on intimate human-machine interaction and associated hazards. Due to the complex management techniques utilized on construction sites, potential workplace hazards cannot be eliminated. Despite, there were increasingly more accidents and fatalities. Therefore, this research was carried out to discover solutions by implementation of IR 4.0 for controlling workers’ safety at construction site. The purpose of this study was to identify the key problems, key factors, and promoting methods implementation of IR 4.0 for controlling workers’ safety at construction site. Questionnaires were used as the tool for data collection in this research to accomplish the goals. In Selangor, 341 G7 contractors contributed to the distribution questionnaire for this study, and 138 of those respondents reported receiving their questionnaire results. The data were analyzed through SPSS to determine the mean, standard deviation and the pie charts, frequency, and percentage values for the respondents’ backgrounds. The findings indicated that the key problems with IR 4.0 were high setup and post-processing costs, as well as high costs of IR 4.0 technology developers’ employment. Enhancing real-time data capture for workers’ safety was one of the key factors of IR 4.0 implementation and promoting methods of IR 4.0 was promoted IR 4.0 technology by regularly controlling workers’ safety. In conclusion, the research offered a wealth of information for effectively regulating employees' safety with the adoption of IR 4.0 at the construction site.